FIKIH FALAKIYAH PERSPEKTIF TEORI ASTRONOMI: Analisis Tinggi Hilal dari Segi Koreksi Semidiameter Bulan - Hidayatullah, Muhammad Syarief (UIN ALAUDDIN MAKASSAR, 2022)
The Altitude of the hilal mar'i has always been a major concern in the concept of hilal visibility in general. The reference for the altitude of the new moon can be found by using the Moon's semi-diameter correction. Falakiyah institutions in Indonesia, when calculating the beginning of the lunar month, always use the Moon's semi-diameter correction to determine the altitude of the new moon that can be seen by observers. Meanwhile, world astronomers do not use this correction in calculating the movement of the Moon. Using the library research method to be able to review library materials and key information documents. An astronomical approach, in order to be able to provide scientific reasons regarding the use of the Moon's semidiameter correction. The sources of reckoning data are the astronomical almanac and ephemeris reckoning of the Ministry of Religion of the Republic of Indonesia, the reference point is the midpoint of the Moon, so all calculations using this data should not change the reference point in the semidiameter correction for the new moon altitude. This change is considered as an inconsistency of the falakiyah reckoning experts. Because, if you use a different semi-diameter correction, it will produce a different value for calculating the altitude of the new moon.